The Structures of Derivatives and Their Semantic Implications in Al-Kawthariyyah Poem Active and Passive Participles as a Model (Journal of the College of Basic Education, 2025)
Interest in morphological components among poets has increased to the extent that they employed them in a deliberate manner throughout the poem, rendering it coherent rather than scattered. Indeed, the role of prominent poets was remarkable, as they consolidated its foundations and created a unique style, subjecting it to morphological refinement rooted in the Qur’an and the Sunnah.The attention given to morphological structures by poets reached an extraordinary level, where such elements were strategically distributed within the poem to maintain cohesion and avoid fragmentation. These morphological features became stronger in poetry, and their meanings matured, allowing the linguistic drive to flow naturally within the poet’s conscience while preserving the spirit of the Arabic language.This research aims to study the semantic significance of these morphological forms and to highlight their implications within the text of the poem